Loss-of-function missense variant of AKAP4 induced male infertility through reduced interaction with QRICH2 during sperm flagella development. Issue 2 (20th August 2021) - Zhang, Guohui; Li, Dongyan; Tu, Chaofeng; Meng, Lanlan; Tan, Yueqiu; Ji, Zhiliang; Cheng, Jiao; Lu, Guangxiu; Lin, Ge; Zhang, Huan; Sun, Jinpeng; Wang, Mingwei; et al.
Abstract: Sperm fibrous sheath (FS) is closely related to sperm maturation, capacitation and motility, and A-kinase anchor protein 4 (AKAP4) is the most abundant protein in sperm FS. Previous studies found incomplete sperm FSs and abnormal flagella in Akap4 knockout mice. Meanwhile, it was reported that the partial deletion in AKAP4 is highly relevant to the dysplasia of the FS in an infertile man, and so far, there is no report about male infertility caused by hemizygous AKAP4 variant. Furthermore, the specific mechanisms of how the variant is relevant to the phenotype remain elusive. In this study, we investigated three multiple morphological abnormalities of the sperm flagella-affected men from three independent families (including one consanguine family) carried hemizygous c.C1285T variant in AKAP4 . The patients carried this variant, which showed dysplastic sperm FS, and the protein expression of AKAP4 was decreased in flagella, which was further confirmed in HEK-293T cells in vitro . In addition, the co-localization and interaction between AKAP4 and glutamine-rich protein 2 (QRICH2) on the molecular level were identified by immunofluorescence and co-immunoprecipitation (CO-IP). The hemizygous c.1285C > T variant in AKAP4 induced decreased protein expression of QRICH2 in spermatozoa. These results suggested that the normal expression of AKAP4 is required for maintaining the expression of QRICH2 and the decreased protein expression of AKAP4 and QRICH2，as well as the interaction between them induced by the hemizygous variant of AKAP4 caused dysplastic fibrous sheath, which eventually led to reduced sperm motility and male infertility.